PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK PEMBELAJARANKOSAKATA BAHASA JEPANG - Utama, Jeri; Hadriana, Hadriana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research is to produce a product in the form of an android-based learning media for learning Japanese vocabulary. Thatbe done at Riau University. This study is a research and development project. The development model used is (1)Potetial problem, (2) Collecting data, (3) Product Desain, (4) Product development, (5) Product revision by supervisor, (6) Product validation,(7) Product revision by material expert and media expert(8) Product test that modified from Sugiyono’s research model. This researcg that be done at Riau University with the subject is active student 3rdgrade in Japanese language study program Faculty of Teacher Training and Education Riau University.. The product feasibility testing stage will be done by two expert, that is material expert and media expert. The course participant also testing the product as user. Data collection techniques used a questionnaires, and descriptive analysis for data analysis.The results of study showed that the interactive multimedia was eligible to be implemented as learning media for3rdgrade student in Japanese language study program Faculty of Teacher Training and Education Riau University.By material expert, the media get an average score 82.5% that means the media is valid to be used for learning process. By media expert, the media get an average score 88.5% that means the media is valid to be used for learning process. And also, product test toward users have been done, that the media get an average score 82.6% that means the media is valid to be used for learning process.KeyWords: Research&Development, Sugyono method, Descrptive amalysis